0)(7t-2)-(-3t+1)=-3(1-3t)

Simple and best practice solution for 0)(7t-2)-(-3t+1)=-3(1-3t) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0)(7t-2)-(-3t+1)=-3(1-3t) equation:



0)(7t-2)-(-3t+1)=-3(1-3t)
We move all terms to the left:
0)(7t-2)-(-3t+1)-(-3(1-3t))=0
We add all the numbers together, and all the variables
0)(7t-3t-3(-3t+1))-2)-1-(=0
We add all the numbers together, and all the variables
-3t+0)(7t-3(-3t+1))-2)-1-(=0

See similar equations:

| 2w–5(w–4)=-13 | | 13(x-1)=5(x-2)+(3x+7) | | -2-13.8x=-8x(6x-1) | | –6a+1=14 | | 3a-4=2a+4 | | -18.17−6.9g−6.96=-2.77−4.3g | | 6p+3=9p-5 | | 30=-p–4p | | n.0.3n=6 | | -3.2q-17.08=-1.8q | | 10=4+6r | | 15m-19-19=20m+17 | | 8x20+5=x | | 1+13n=12n+19 | | 1000y-460=3(100y+80) | | 4(4+p)=28 | | ×+4+3x=-12 | | 0,5x+x=9 | | -16c=-15c-12 | | (-9)=s+ | | -4=9w–5w | | 3/4(12c-4)=15c-15 | | -87=-9r+2r–17 | | 15+5(4+y)=-20 | | -11=5y+4= | | -5r=-4r+5 | | -5r=-4r | | -56=6(u–1)+4u | | -6-6p=-4p+10 | | 7r–15=-50 | | y+4/5=1/7 | | 8q+10=-2+4+9q |

Equations solver categories